The influence of sulfuric environments on concretes elaborated with sulfate resistant cements and mineral admixtures. Part 2: Concrete exposed to Magnesium Sulfate (MgSO4) - Bernal Camacho, Jesús Manuel; Mahmoud Abdelkader, S.; Reyes Pozo, E.; Monteagudo Viera, S. (Revista de la Construcción. Journal of Construction, 2013)
The present work studies the resistant of the concrete against magnesium sulfate (MgSO4) and compare the results with values obtained previously of the same concretes exposed to sodium sulfate (Na2SO4). Thus, it is possible analyze the influence of the cation type. To that end, four different concrete mixes were made with sulfur resistant cement and mineral admixtures (silica fume, fly ash and blast furnace slag). The concretes were submerged for different period in magnesium sulfate (MgSO4). After that, different tests were carried out to define mechanical and microstructural properties. The results obtained were compared with reference values of concretes cured in calcium hydroxide [Ca(OH)2]. According to the results, the concrete with blast furnace slag presented the best behavior front MgSO4, meanwhile the concretes with silica fume and fly ash were the most susceptible. The resistance of the concrete with blast furnace slag could be attributed to the characteristics of the hydrated silicates formed during the hydration time, which include aluminum in the chemical chain that hinder its chemical decomposition during the attack of magnesium. The magnesium sulfate solution was most aggressive than sodium sulfate solution.